Detection and quantification of long chain fatty acids in liquid and solid samples and its relevance to understand anaerobic digestion of lipids - Neves, L. (2009)
A method for long chain fatty acids (LCFA) extraction, identification and further quantification by gas chromatography was developed and its application to liquid and solid samples collected from anaerobic digesters was demonstrated. After validation, the usefulness of this method was demonstrated in a cow manure digester receiving pulses of an industrial effluent containing high lipid content. From the LCFA analysis data it was showed that the conversion of oleic acid, the main LCFA fed to the reactor, by the adapted biomass became faster and more effective along the successive pulses. Conversely, the accumulation of palmitic acid in the solid phase suggests that degradation of this LCFA, under these conditions, is less effective.